Comparative Studies on the Use of Binary and Ternary Combinations of Various Acidifying Agents for the Reduction of Soil pH. Issue 1 (2nd January 2016) - Fazal, Tanzeela; Ismail, Bushra; Khan, Asad Muhammad; Khan, Rafaqat Ali; Naqvi, Amir Abbas Shah; Hamid, Farrukh Siyar; Sabir, Muhammad Amjad; Faridullah,; Khan, Abdur Rahman
ABSTRACT: The present study deals with the effects of addition of sulfur along with other acidifying agents for their ability to lower and maintain the pH in a given range for a longer period of time. The chemicals were subjected to batch test individually and in combinations. Treatments were applied to three soils of different textures: sandy clay loam, clay loam, and silt loam. A 1:1 soil/water paste along with the added amendment was maintained at room temperature for 2 months. Most of the chemical treatments lowered the pH significantly. Combinations containing S/Al2 (SO4 )3 /H2 SO4, S/Al2 (SO4 )3 /H2 O2, and S/H2 O2 /H2 SO4 were found to be very effective in lowering the pH. The soil pH remained acidic for 2 months, indicating the suitability of chemically amended soil for the plantations requiring acidic soil pH.